GASTRIC CARCINOMA WITH OSSEOUS METAPLASIA IN A DOG - Amorim, Irina Ferraz; Lopes, Celia; Gil da Costa, Rui M; Faustino, Augusto MR; Gartner, Fatima; Dias Pereira, Patricia (Archives of Veterinary Science, 2012)
This report describes an unprecedented case of a gastric carcinoma with osseous metaplasia in a 8-year-old male standard poodle. An exploratory laparotomy revealed a firm yellowish nodular mass in the pyloric region. The lesion was surgically removed and submitted for current histological examination. Immunohistochemistry was performed employing monoclonal antibodies for pan-cytokeratin, vimentin, smooth muscular <span lang="EN-GB" style="font-family: Symbol; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT; mso-bidi-language: AR-SA; mso-ascii-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-char-type: symbol; mso-symbol-font-family: Symbol;">a-actin and BMP-2/4. The mass consisted in neoplastic proliferation of epithelial cells, arranged in a tubular or acinar pattern and supported by scirrhous stroma, with mucin production and multiple foci of heterotopic ossification. Neoplastic epithelial cells showed strong positive immunostaining for AE1/AE3 and BMP-2/4, although they were negative for both vimentin and <span lang="EN-GB" style="font-family: Symbol; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT; mso-bidi-language: AR-SA; mso-ascii-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-char-type: symbol; mso-symbol-font-family: Symbol;">a-actin. Histopathological findings suggested that the bone tissue may be primarily originated from neoplastic epithelial cells which directly circumscribe the osseous metaplasia foci.